Peak age incidence of Breast Cancer: our experience of 754 Patients at Breast Lab of FJMC/Sir Ganga Ram Hospital Lahore - ANDLEEB KHANAM, AYESHA SHAUKAT, MUHAMMAD ASLAM, (Journal of Fatima Jinnah Medical University, 2018)
Amis and objective: To find out the peak age incidence of Breast Cancer in our patient and comparing it with the western incidence. Study Design: It was a prospective clinicapathological study. Material and Method: All patients reporting to the Breast lab with histopathological diagnosis of Breast Cancer. Result: A total 754 patients were included in the study. They were divided into seven age groups and peak age incidence was established. Conclusion: In our study the peak age incidence was group of 31 to 40 year, in our patient Breast Cancer was predominately a premenopausal disease.